Pengaruh Disiplin Kerja dan Keselamatan Kerja Terhadap Efektivitas Kerja Personel Unit PKP-PK - Bagas Adhi Pradana; Agung Muhammad Rizky Firmansyah; Nawang Kalbuana (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Airplane Accident Assistance and Fire Fighting (PKP-PK) is a unit at the airport that is responsible for handling aviation emergencies and fires. This research discusses the influence of work discipline and work safety on the work effectiveness of PKP-PK unit employees at airports. Work discipline itself means attitudes and behavior that show compliance and adherence to the rules, norms, procedures and work ethic established in the workplace. Meanwhile Occupational safety itself is a series of actions, policies and procedures implemented to protect the health and safety of employees in the workplace. The aim of this research is to analyze the influence of employee work discipline and work safety on the effectiveness of the PKP-PK work unit. This research also aims to determine the effectiveness of the work of firefighters regarding obstacles and the efforts made to overcome these obstacles.The method used in this research is library research, which involves collecting and analyzing data from various relevant literature sources. This research focuses on previous studies regarding work discipline and work safety on work effectiveness in the PKP-PK unit. The research results show that good work discipline and safety have a positive effect on the work effectiveness of the PKP-PK firefighting unit employees. Discipline that is embedded in the souls of every employee increases work effectiveness and enthusiasm for work, so that responses to emergency situations can be carried out quickly and effectively. Therefore, there is a need for better personnel training and more detailed safety equipment readiness to improve operational performance.